2020
DOI: 10.1021/acs.iecr.0c04727
|View full text |Cite
|
Sign up to set email alerts
|

Steam Cracking Coke Properties and Their Influence on Furnace Run Length Predictions: Experimental and Modeling Study

Abstract: Although coke formation is one of the most important problems that the steam cracking process still faces, the properties of the formed coke have hardly been studied over the past decade. For some of them, orders of magnitude differences have been reported. Therefore, state-of-the-art measurement techniques have been used on industrially relevant samples obtained at laboratory and industrial scale for ethane and naphtha cracking. The feedstock type does play an important role, reflected in, for example, factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
(137 reference statements)
0
6
0
Order By: Relevance
“…59,60 The heat flux from the furnace to the radiant tubes is required to perform the industrial furnace simulation, which acts as a set of boundary conditions for the simulation. The incident heat flux profile obtained by using the 1D furnace model 61,62 is implemented in this case. The framework of COILSIM1D consists of two parts: a microkinetic model and a reactor model.…”
Section: Run Length Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…59,60 The heat flux from the furnace to the radiant tubes is required to perform the industrial furnace simulation, which acts as a set of boundary conditions for the simulation. The incident heat flux profile obtained by using the 1D furnace model 61,62 is implemented in this case. The framework of COILSIM1D consists of two parts: a microkinetic model and a reactor model.…”
Section: Run Length Simulationmentioning
confidence: 99%
“…These two severity indices unambiguously determine the product yields of the given feed. , The heat flux from the furnace to the radiant tubes is required to perform the industrial furnace simulation, which acts as a set of boundary conditions for the simulation. The incident heat flux profile obtained by using the 1D furnace model , is implemented in this case.…”
Section: Run Length Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the measurement of coke properties is outside the scope of the current study and the values provided in the literature are used, an accurate assessment of coke properties is important due to its effect on run length. Geerts et al [ 6 ] analyzed the sensitivity of run length to the coke properties and stressed the importance of an accurate value of the coke thermal conductivity. They also showed that thermal conductivity of coke increased as the temperature increased, in which thermal conductivity of coke was measured as 8.1 and 8.6 W/(m · K) for two different times on‐stream of a naphtha cracker.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…[ 1 ] Similarly, this was also reported in a recent review paper by Symoens et al [ 5 ] which discussed some aspects of coke formation and deposition on the coils. The thermal conductivity of coke was further illustrated in the work of Geerts et al [ 6 ] They report a huge differences in run length of naphtha cracking furnaces, for example, from 2 to 30 weeks, when coke thermal conductivity increases from 4.5 to 14 W/(m · K), respectively.…”
Section: Introductionmentioning
confidence: 99%